The Effectiveness of an Internet Support Forum for Carers of People With Dementia: A Pre-Post Cohort Study - McKechnie, Vicky; Barker, Chris; Stott, Josh (JMIR Publications, 2014)
BackgroundThe well-being of informal carers of people with dementia is an important public health issue. Caring for an elderly relative with dementia may be burdensome and stressful, and can negatively affect the carer's social, family, and professional life. The combination of loss, the physical demands of caregiving, prolonged distress, and biological vulnerabilities of older carers may compromise their physical health, increase social isolation, and increase the risk of anxiety and depressive disorders. Caregiver stress is also linked to negative outcomes for the recipient of care and costs to society, including increased nursing home and hospital admissions. Consequently, carer support interventions are an important component of dementia care. Computer-mediated carer support offers a range of potential advantages compared to traditional face-to-face support groups, including accessibility and the possibility of tailoring to meet individual needs, but there has been little research on its effectiveness so far. ObjectiveThis mixed-methods study examined the impact of a well-respected UK-based online support forum for carers of people with dementia. MethodsA total of 61 new forum users completed measures of anxiety (7-item Generalized Anxiety Disorder scale, GAD-7), depression (9-item Patient Health Questionnaire, PHQ-9), and quality of relationship with the person with dementia (Scale for the Quality of the Current Relationship in Caregiving, SQCRC), at baseline and again after 12 weeks of forum usage, within a pre-post design. In addition, 8 participants were interviewed about their experiences with using the forum. ResultsThere was an improvement in the quality of the relationship with the person with dementia (SQCRC: P=.003). There was no change in users' depression (PHQ-9) or anxiety (GAD-7) over the 12-week study period. Interview participants reported a range of positive experiences and benefits from using the forum. Limited negative experiences were also reported. ConclusionsMany of the reported experiences and benefits are unique to online peer support. Further research into online peer support for carers of people with dementia is needed to clarify who benefits under what conditions.